Resource Management in Large Cloud Environments Using Lyapunov and Heuristic Algorithm - Therasa.T; V. Vasanth; Vidhya. M (International Journal of Computer Sciences and Engineering, 2014)
Powerful source management for a large-scale reasoning environment is a significant issue. Power consumption consists of a significant fraction of total operating price in information facilities. Resource allowance among sites/applications, dynamically adjusts the allowance to load changes and machines both in the number of physical machines and sites/applications. A method that determines an optimal remedy without considering memory restrictions and prove correctness and unity properties. Increase that method to provide an efficient heuristic remedy for the complete issue, which includes reducing the price for adjusting an allowance. The method consistently carries out on dynamic, local input and does not require global synchronization, the heuristic criteria to do. Utilizing available power storage space capability in information facilities to reduce electric bill under real-time electricity market. Lyapunov optimization technique is applied to design a criterion that accomplishes an precise compromise between price preserving and power storage space capacity.